Effectivity Analysis of Chosen Numerical Methods for Solution of Mechanical Systems with Uncertain Parameters - Robert Bednar; Milan Saga; Milan Vasko (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with usability and efficiency problem for the chosen solution methods for mechanical systems with structural uncertainties, which are significantly influencing the analysis results and the analysis itself. In the centre of interest will be the chosen approaches and methods. An application of the chosen approaches is presented – the first one, a simple combination of only inf-values or only sup-values; the second one presents full combination of all inf-sup values; the third one uses the optimizing process as a tool for finding out an inf-sup solution and last one is Monte Carlo technique as a comparison tool.